Blood Group Discrepancies at a Regional Blood Center - Hayedeh Javadzadeh Shahshahani; Azam Hayati (International Journal of Hematology-Oncology and Stem Cell Research, 2020)
Background: Blood group testing is an important part of supplying safe blood components in blood transfusion centers. Blood group discrepancy develops when reactions in forward grouping do not correspond with reverse grouping or if the preceding and recent results do not match. This study aimed to evaluate ABO blood group discrepancies among blood donors of Yazd, Iran. Materials and Methods: In this cross-sectional study, data of blood donors were obtained from the integrated database of Yazd Blood Transfusion Center during a period of eight years (2010 – 2017). Tube testing was used for determining the ABO blood groups. A serological workup was performed for diagnosis and determination of the discrepancy. Confirmation of the results was accomplished by the reference laboratory of immunohematology. Results: Blood group discrepancies were detected in 130 (0.04%) out of 322,222 donations. Technical/Clerical errors leading to ABO discrepancy were noticed in 12 (9.3%) cases. The most frequent cause of ABO discrepancies in forward grouping was subgroups of A Antigen (44.6%) and in reverse grouping was cold autoantibody (23.9%). There were 11 (8.4%) cases with alloantibodies. Two blood donors with rare Bombay phenotype and p blood group were also identified. Conclusion: For minimizing Technical/Clerical errors, accurate blood donor or sample identification programs should be implemented. All cases of blood group discrepancies should be carefully investigated, and blood donors should be informed appropriately.